The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1183/09031936.00101606
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status, asthma and chronic bronchitis in a large community-based study

Abstract: The present study investigated the relationship between socioeconomic status, using measures of occupational class and education level, and the prevalence and incidence of asthma (with and without atopy) and chronic bronchitis using data from the European Community Respiratory Health Survey (ECRHS).Asthma and chronic bronchitis were studied prospectively within the ECRHS (n59,023). Incidence analyses comprised subjects with no history of asthma or bronchitis at baseline. Asthma symptoms were also assessed as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
83
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 27 publications
(46 reference statements)
18
83
2
3
Order By: Relevance
“…However, our study could not show any association of chronic bronchitis with male gender, despite 0% prevalence smoking in females and 17% prevalence smoking in males. Current evidence suggests that male gender is a potential risk factor for chronic bronchitis, fundamentally because of relatively high prevalence of smoking amongst males [28,32]. What was further intriguing was that, even exposure to biomass fuel smoke which has been regarded as important risk factor for respiratory morbidities [33] did not contribute to chronic bronchitis in slum women.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, our study could not show any association of chronic bronchitis with male gender, despite 0% prevalence smoking in females and 17% prevalence smoking in males. Current evidence suggests that male gender is a potential risk factor for chronic bronchitis, fundamentally because of relatively high prevalence of smoking amongst males [28,32]. What was further intriguing was that, even exposure to biomass fuel smoke which has been regarded as important risk factor for respiratory morbidities [33] did not contribute to chronic bronchitis in slum women.…”
Section: Discussionmentioning
confidence: 92%
“…This is contradictory to what has been observed before. Studies have shown that prevalence of chronic bronchitis is positively related to age [28,29,32], which has been attributed to changes in immune system and negative impact of age on lung physiology. One approximate explanation to the contrary observations in our study could be, that exposures to adverse slum environmental dynamics [1,5] may trigger recurrent induction of immune processes in lungs of slum residents which could compromise lung growth during developmental stages such as childhood [34].…”
Section: Discussionmentioning
confidence: 99%
“…Subjects in the low occupational class (incident risk ratio (IRR) 1.4; 95%CI 1.2-1.7) and education group (IRR 1.3; 95% CI 1.1-1.6) had higher mean asthma scores than those in higher socioeconomic groups and that lower socioeconomic groups tended to have a higher prevalence and incidence of asthma, particularly higher mean asthma scores [42]. In a study by Basagana et al [41] using the same survey found similar results, that asthma prevalence was higher in lower socioeconomic groups, whether defined by educational level or social class regardless of atopic status.…”
Section: Asthmamentioning
confidence: 95%
“…This last factor has been associated with a variety of differential health impacts, including premature mortality, asthma, and chronic bronchitis (Ellison-Loschmann et al, 2007). Traffic exposures are often higher in neighborhoods of low SES in the United States (Finkelstein et al, 2005;Ponce et al, 2005), but not necessarily in Europe (Forastiere et al, 2007).…”
Section: Problems Of Confounding Collinearity and Measurement Errormentioning
confidence: 99%